IMPLEMENTASI NILAI-NILAI ISLAM PADA KARYAWAN KSPPS HUDATAMA SEMARANG - W Niati, Annisa Lufth; Mas’ud, Fuad (Diponegoro Journal of Management, 2018)
In a business activity the role of leaders and employees is very influential in achievingthe company's vision and mission, almost all activities in the company involve the role of employees in it. The factor of human resources is an important factor in the development of the company. This research will discuss implementation of Islamic values in the understanding of employees which has an impact on improving employee performance, especially in Sharia Cooperatives.The purpose of this study is to describe the response of employees and leaders to the performance of KSPPS Hudatama employees and analyzing the extent to which employees and leaders understand the values of Islam KSPPS Hudatama.The method used is qualitative method with   case study approach. The reason for selecting these method is so that research can be focused and can be done in depth to find out employees' understanding of working in accordance with Islamic values KSPPS Hudatama and impact on employee performance. From the research results showed that improving  employee  performance  is  not  only  proven  through  numerical  productivity growth reports only but also can shape the behavior of its employees in accordance with Islamic values KSPPS Hudatama. The increase in employee performance was also assisted by the employee training held by KSPPS Hudatama.